2014
DOI: 10.1007/978-3-319-09156-3_37
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Refactoring Large-Scale Industrial Systems to Efficiently Improve Source Code Quality

Abstract: Abstract. Refactoring source code has many benets (e.g. improving maintainability, robustness and source code quality), but it takes time away from other implementation tasks, resulting in developers neglecting refactoring steps during the development process. But what happens when they know that the quality of their source code needs to be improved and they can get the extra time and money to refactor the code? What will they do? What will they consider the most important for improving source code quality? Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
(23 reference statements)
3
16
0
Order By: Relevance
“…However, further research work show that the idea can also be applied to other purposes [3], such as improving performance, security, and reliability. In fact, as our previous research [4] indicates, developers often tend to do refactorings to fix coding issues that clearly affect the quality of the system, instead of refactoring code smells or antipatterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, further research work show that the idea can also be applied to other purposes [3], such as improving performance, security, and reliability. In fact, as our previous research [4] indicates, developers often tend to do refactorings to fix coding issues that clearly affect the quality of the system, instead of refactoring code smells or antipatterns.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting and recent study on refactoring has been proposed by Szoke et al [16], where they provide answers to different questions on refactoring best practices of large scale industrial systems. A very interesting and complete survey on software refactoring in general has been proposed by Mens et al [12], and relevant considerations on how refactoring is done have been made by Murphy-Hill [13].…”
Section: Related Workmentioning
confidence: 99%
“…Any of them might be a good solution. However, we will choose coding issues as the main target of our automated refactorings because our preliminary study [27] suggested that this is what developers want the most. To identify coding issues we choose the well known PMD static source code analyzer.…”
Section: Finding Refactoring Suggestionsmentioning
confidence: 99%